2018
DOI: 10.3390/nu10030286
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-Oligosaccharide/Polidextrose Enriched Formula Protects against Respiratory Infections in Infants at High Risk of Atopy: A Randomized Clinical Trial

Abstract: Background: Early nutrition affects the risk of atopy and infections through modifications of intestinal microbiota. The Prebiotics in the Prevention of Atopy (PIPA) study was a 24-month randomised, double-blind, placebo-controlled trial. It aimed to evaluate the effects of a galacto-oligosaccharide/polydextrose (GOS/PDX)-formula (PF) on atopic dermatitis (AD) and common infections in infants who were born to atopic parents and to investigate the relationship among early nutrition, gut microbiota and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 33 publications
(53 reference statements)
2
55
0
1
Order By: Relevance
“…In a randomized clinical trial, a galacto-oligosaccharide/polidextrose enriched formula protected infants who were born to atopic parents from respiratory infections. It increased the colonization of the protective bacteria including Bifidobacteria and Clostridium cluster I (Ranucci et al, 2018).…”
Section: Regulating Inflammation and Immune-responsementioning
confidence: 99%
“…In a randomized clinical trial, a galacto-oligosaccharide/polidextrose enriched formula protected infants who were born to atopic parents from respiratory infections. It increased the colonization of the protective bacteria including Bifidobacteria and Clostridium cluster I (Ranucci et al, 2018).…”
Section: Regulating Inflammation and Immune-responsementioning
confidence: 99%
“…A large study found the galacto-oligosaccharide/polydextrose (GOS/PDX)-formula to have a significant protective effect against respiratory infections in young infants. 72 Yet, another large trial study reported no effect of a GOS-containing infant formula on the rate of infections or allergic diseases in infants, even though a clear prebiotic effect was demonstrated by changes in feacal characteristics. 73 Moreover, a RCT by Niele et al 74 , including 113 preterm infants, found no benefits of short-term prebiotic mixture supplementation of neutral and acidic oligosaccharide on the incidence of infectious and allergic conditions in infants during their first year of life.…”
Section: Therapeutic Interventions Targeting the Lung Microbiomementioning
confidence: 99%
“…Several intervention studies have reported the functional benefit of adding prebiotic oligosaccharides to infant formula. More specifically, specific prebiotic oligosaccharides have been shown to ameliorate the development of allergies as well as reduce the impact of pediatric infections ( 4 , 5 , 73 75 ). In this regard, the immune modulating effect that seems to decrease the risk on developing atopy and allergy, also may lower the infection risk in neonates, which is suggestive for basic immune modulation early in life.…”
Section: Human Milk Oligosaccharide Impact In Vivomentioning
confidence: 99%
“…Although growth and 2′-FL uptake were similar between formula receiving infants and as seen in breastfed infants, the possible functional benefits regarding immune development and/or infection susceptibility related to a single oligosaccharide are however not extractable from these studies. Therefore, the identification and understanding of protective elements in human breast milk decreasing infant's susceptibility to infection remains limited ( 75 ).…”
Section: Human Milk Oligosaccharide Impact In Vivomentioning
confidence: 99%